THE INFLUENCE OF STUDENT LEARNING INTEREST ON INDONESIAN LANGUAGE LEARNING - Santi, Meldia; Rafidhah Hanum; Fakhrul Rijal (Jurnal Ikhtibar Nusantara, 2026)
This study aims to determine the effect of student learning interest on Indonesian language learning. Learning interest is an internal factor that plays a crucial role in enhancing the effectiveness of the learning process. The research method used was a quantitative approach with descriptive statistical analysis techniques, validity tests, reliability tests, and normality tests using the SPSS program. The study sample consisted of 27 students. The results showed that student learning interest was in the high category with an average score of 78.52. The validity test results showed that all 20 instrument items were valid, while the reliability test obtained a Cronbach’s Alpha value of 0.912, which is categorized as highly reliable. The normality test showed a significance value of 0.200 (>0.05), indicating that the data were normally distributed and suitable for parametric analysis. These findings indicate that the research instrument was of good quality and the data met statistical assumptions. Thus, student learning interest has significant potential to support the success of Indonesian language learning, and therefore, enhancing it needs to be a priority in the learning process at school.